Experimental study on tensile performance of horizontal joint bolted connections in fully assembled modular construction reinforced concrete - RAN Mingming; KOU Guangyun; XIONG Feng; ZHANG Dongdong; LI Wei (工程科学与技术)
ObjectiveConcrete modular buildings have the advantages of superior structural integrity, high living comfort, and low construction and maintenance costs. In concrete module structures, the connections between modules critically determine the overall structural performance. The fully assembled modular construction reinforced concrete (FAMC-RC) system is a structural system composed of prefabricated concrete modules assembled through bolted connections, where horizontal connection joints primarily consist of high-strength bolts, steel spacers, and threaded sleeves. Current research on the performance of horizontal connections in this system remains limited, particularly regarding load-transfer mechanisms, joint configurations, and mechanical behavior. This study conducted tensile tests on 13 FAMC-RC horizontal bolted connection specimens with varying parameters to investigate their tensile load-bearing capacity and deformation characteristics.MethodsThirteen horizontal connection joint specimens were designed with key design parameters including concealed beam height, edge distance width, bolt-hole diameter, and bolt-hole geometry. Each specimen contained a pre-embedded hand-hole bolted connection joint. Monotonic tensile loading and forward cyclic loading tests were performed on the specimens using a vertical actuator. To better simulate real engineering conditions, a rectangular steel plate was pre-embedded at the specimen base and anchored to a rigid ground surface through foundation bolts to provide vertical constraints. A box-section loading beam was fixed to the vertical actuator and connected to the specimen via high-strength bolts for vertical load application. Monotonic tensile loading was controlled through a force-displacement hybrid method, while forward cyclic loading was displacement-controlled. The tests were terminated when the tensile load-bearing capacity of the specimens decreased to 85% of the peak load or when significant failure phenomena were observed.Results and Discussions Five distinct failure modes were observed in thirteen horizontal connection joint specimens under tensile loading: (I) thread stripping or fracture of Grade 8.8 bolts, (II) conical punching shear failure of concrete above the operating hand-hole, (III) concrete crushing followed by conical punching shear failure above the operating hand-hole, (IV) net-section tensile failure at the cross-section above the operating hand-hole, and (V) anchorage failure between embedded steel plates and vertical reinforcement. In Mode I, when the load reached 180 kN, the tensile load-bearing capacity growth rate was significantly reduced, accompanied by a distinct plateau segment in the load-displacement curve, indicating yielding-strengthening behavior of Grade 8.8 bolts. Thread stripping failure occurred at 200 kN. Modes II and III were both categorized as punching shear failures, differentiated by the presence of a 100-mm-height concrete crushing zone prior to punching shear in Mode III. Specifically, Mode II was characterized by the sudden expansion of progressively extending diagonal cracks above the operating hand-hole forming dominant failure cracks, corresponding to the maximum peak load-bearing capacity. Mode III exhibited pronounced concrete crushing and spalling above the operating hand-hole prior to punching shear failure. Under sustained loading, diagonal cracks rapidly propagated along both edges of the crushing zone, ultimately leading to punching shear failure, with a relatively smaller peak load-bearing capacity. According to the calculation theory for punching shear failure bearing capacity, the reduced peak load-bearing capacity of Mode III compared to Mode II was attributed to the reduction in the effective height of the punching shear cone caused by the crushing zone, consequently resulting in decreased anti-punching shear capacity. In Mode IV, when the load was increased to 134.2 kN, abrupt fracture failure of the concrete at the cross-section above the operating hand-hole of the specimen was observed, with limited cracking. This failure mechanism was attributed to the reduced edge distance width of the specimen, resulting in diminished net-section bearing capacity. Mode V, attributed to poor welding quality between vertical steel bars and embedded steel plates, was deemed non-representative of actual structural behavior. Load-displacement curves revealed four consistent stages across all failure modes: prestress loss, elastic loading, working with cracks, and brittle failure. No alteration in failure modes was observed in specimens subjected to forward cyclic loading, and identical mechanical behavior was demonstrated relative to specimens under monotonic loading protocols. The experimental results indicated that the tensile mechanical behavior of the horizontal connection joints was governed by multiple parameters including edge distance width (B), concealed beam height (H), bolt-hole diameter (D), and bolt-hole geometry. When H was 250 mm, an increase in B from 160 mm to 325 mm was found to enhance the peak load-bearing capacity by 117% and initial stiffness by 61%, while for H = 200 mm, the same B variation improved the capacity by 20% and stiffness by 72%. Both parameters entered stabilized states with negligible increments when B exceeded 325 mm. This phenomenon suggested that exceeding 325 mm in edge distance width was sufficient to ensure full utilization of the joint's tensile performance. For H increments from 200 mm to 250 mm (25 mm intervals), the peak load-bearing capacity exhibited quasi-linear growth of 23% and 24%, whereas the initial stiffness showed limited improvements of only 7% and 4%. This disparity confirmed significantly higher sensitivity of load-bearing capacity to H compared to stiffness, rendering H augmentation an inefficient strategy for stiffness enhancement. Increasing D from 25 mm to 32 mm and subsequently to 40 mm resulted in peak load-bearing capacity reductions of approximately 3% and 22%, respectively, with stiffness variations confined to ±5%, demonstrating that D ≤32 mm preserved optimal joint performance. Specimens with cylindrical bolt-holes demonstrated the highest peak load-bearing capacity and initial stiffness. Relative to cylindrical configurations, tapered bolt-holes reduced capacity and stiffness by 14% and 17%, while cylindrical-tapered hybrid bolt-holes caused 7% and 6% reductions, respectively. Punching shear failure was identified as the ideal failure mode for this joint system. A punching shear capacity calculation formula was proposed, with discrepancies between calculated and experimental values maintained within 15%, and the calculation method was demonstrated to be rational.ConclusionsThe results indicated that the horizontal bolted connection joint under tensile loading could develop failure modes including bolt thread stripping, concrete punching shear failure, combined concrete crushing-punching shear failure, and net-section tensile failure. The tensile performance of the joint was governed by edge distance width (B), concealed beam height (H), bolt-hole diameter (D), and bolt-hole geometry. Within defined thresholds, increasing the dimensions of B and H could effectively enhance peak load-bearing capacity and initial stiffness, whereas exceeding these thresholds resulted in negligible improvements. Larger bolt-hole diameters and smaller steel washer dimensions led to a reduction in the contact area between the washer and concrete, thereby decreasing the peak load-carrying capacity and initial stiffness. Specimens with cylindrical bolt-holes exhibited the highest peak capacity and stiffness, followed by cylindrical-tapered hybrid and tapered configurations. Engineering recommendations were established: B ≥ 300 mm, H ≥ 250 mm, D ≤ 32 mm, and cylindrical-tapered bolt-holes could be adopted for load demands ≤ 180 kN to reduce installation complexity. The proposed punching shear capacity calculation formula for the joint was validated to exhibit sufficient safety margins, with its computational methodology confirmed as rationally justified.